Glanzmann Thrombasthenia 10 Years Later: Progress Made and Future Directions - Nurden, Alan T.; Nurden, Paquita (Seminars in Thrombosis and Hemostasis, 2024)
Glanzmann thrombasthenia (GT) is the most common inherited platelet disorder (IPD) with mucocutaneous bleeding and a failure of platelets to aggregate when stimulated. The molecular cause is insufficient or defective αIIbβ3, an integrin encoded by the ITGA2B and ITGB3 genes. On activation αIIbβ3 undergoes conformational changes and binds fibrinogen (Fg) and other proteins to join platelets in the aggregate. The application of next-generation sequencing (NGS) to patients with IPDs has accelerated genotyping for GT; progress accompanied by improved mutation curation. The evaluation by NGS of variants in other hemostasis and vascular genes is a major step toward understanding why bleeding varies so much between patients. The recently discovered role for glycoprotein VI in thrombus formation, through its binding to fibrin and surface-bound Fg, may offer a mechanosensitive back-up for αIIbβ3, especially at sites of inflammation. The setting up of national networks for IPDs and GT is improving patient care. Hematopoietic stem cell therapy provides a long-term cure for severe cases; however, prophylaxis by monoclonal antibodies designed to accelerate fibrin formation at injured sites in the vasculature is a promising development. Gene therapy using lentil-virus vectors remains a future option with CRISPR/Cas9 technologies offering a promising alternative route.
Keywords: Glanzmann thrombasthenia; αIIbβ3 integrin; biology; mutations; prophylaxis; gene therapy